Occlusal Changes Following Posterior Tooth Loss in Adults. Part 2. Clinical Parameters Associated with Movement of Teeth Adjacent to the Site of Posterior Tooth Loss - Helen L. Craddock, PhD, M Dent Sci, BDS, MFDS, MRD, FDS (Journal of Prosthodontics, 2007)
Much anecdotal evidence is available on tooth positional changes following loss of an adjacent tooth, but only a few studies are available